Fungsi Kehumasan dalam Membangun Citra Lembaga Penyiaran Publik Televisi Republik Indonesia (LPP TVRI) Stasiun Kalimantan Timur - Octavia, Ananda Gamas; Juwita, Rina (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
LPP TVRI East Kalimantan Station, which once had great power over Indonesian television, slowly began to decline. LPP TVRI East Kalimantan Station has a goal to improve the image of the institution. The purpose of this research is to find out the public relations function and strategies by LPP TVRI East Kalimantan Station in order to build their image and evaluate their strategies. This research uses a qualitative approach method and used Image Restoration Theory. The results showed that LPP TVRI East Kalimantan Station made strategic efforts in accordance with the assumptions of image restoration theory. These strategies include socializing to not broadcasting discrimination, forming Fopersi, promoting through new media content, conducting assessments in employee recruitment, welcoming and accompanying guests to represent their image. It is undeniable that LPP TVRI East Kalimantan Station has not been maximized in applying its strategies because it does not yet have its own public relations division in implementing its public relations functions, resulting in overload in carrying out its duties. It is important for LPP TVRI East Kalimantan Station consistently implementing its strategies so they can achieve the goal of building a positive image and strengthening its role as a unifying medium for the nation.